Monitoring of spatiotemporal changes in ecosystem service functions and analysis of influencing factors in Pingtan Island - Jiajia Xu; Xiaofang Jiang; Hai Liu; Feijian Yin; Yuting Xu; Changhao Gao (Ecological Indicators, 2024)
In response to the needs of national ecological construction, especially the construction of high-quality marine space and reasonable use of the marine environment, Pingtan Island as a demonstration area of China's environmental construction, this study evaluates the quality of its ecological environment, which provides reference for the protection of the future ecological environment. In this study, CASA (Carnegie-ames-stanford approach), RUSLE (Revised universal soil loss equation) and InVEST (Integrated valuation of ecosystem services and trade-offs) models were selected for ecological environment assessment in the Pingtan Island. The NPP (Net primary productivity) calculated by CASA model, soil erosion data calculated by RUSLE and habitat quality, total carbon, water yield, and sediment delivery ratio calculated by InVEST model showed that the ecological environment quality and ecological service function of the study area had a weakening trend from 2000 to 2010. In particular, there was a tendency to weaken the water yield and sediment delivery ratio in the Pingtan Island between 2000 and 2010. The weakening trend during 2010 and 2020 was much higher than that during 2000 and 2010. The main influencing factor of each ecological service function is NDVI, which indicates that the degree of vegetation cover is the key factor determining the ecological service function. The impact of GDP and population on the ecological service functions is also large, which indicates that with the acceleration of urbanization, the ecological service function of the research area has been negatively affected. Changes in ecological services and ecological restoration functions are significant for local sustainable development.